Integrated dielectric-electrode layer for triboelectric nanogenerator based on Cu nanowire-Mesh hybrid electrode. (May 2019) - Zhou, Qitao; Kim, Jong-Nam; Han, Kwan-Woo; Oh, Se-Woong; Umrao, Sima; Chae, Eun Jung; Oh, Il-Kwon
Abstract: Morphological engineering of nano- and micro-surface patterns has been considered as a key design element to achieve superior output performances in triboelectric energy harvesters. Most previous studies have focused on the surface engineering of dielectric materials rather than electrodes. In this study, a hierarchically three-dimensional (3D) copper nanowire-copper Mesh hybrid electrode (Cu NW-Cu Mesh) is reported for developing a high-performance and structurally reliable triboelectric nanogenerator (TENG). The hierarchical electrode has been embedded into a dielectric thin layer of polydimethylsiloxane (PDMS), resulting in an integrated dielectric-electrode layer that has much better structural reliability to repeatable impacts and inherits the roughened morphology of the Cu NW-Cu Mesh. The PDMS sealed Cu NW-Cu Mesh can be widely used in vertical contact-separation mode, single electrode mode, and wind-driven TENGs. Serially connected four hundred green LEDs can be lighted by free fall of a large size Cu NW-Cu Mesh based single electrode TENG. By tapping the large size TENG, a capacitor can be charged and used to power an electronic watch. The results indicate that the proposed integrated dielectric-electrode layer can be used as an effective mechanical energy harvester requiring both structural reliability and high output power under strong impacts due to large amplitude oscillations based on fluid-structure coupled dynamic instabilities. Graphical abstract: PDMS sheathed 3D hierarchical Cu NW-Cu Mesh has been synthesized as an integrated dielectric and electrode layer for different modes of high performance triboelectric nanogenerators (TENGs).fx1 Highlights: A 3D hierarchical Cu NW-Cu Mesh was fabricated for electrode materials of TENG. An integrated dielectric-electrode layer was fabricated by easily spraying of PDMS. The integrated dielectric-electrode layer was be used in various modes of TENGs. A large size integrated dielectric-electrode layer worked as a single electrode TENG. A wind-driven TENG with this integrated layer showed high output power.